Instructions for all students - Morgan, Nancy Battista; Magna Systems, Inc. (Illionois : Magna Systems Inc., 2006)
This DVD program and accompanying workshop manual will give beginning teachers the background and skills to become successful teachers. It will show how to plan and prepare meaning instruction; use instructional strategies that help al students; put into effect proven classroom management skills; and communicate and grow as a professional
Title from title screen
Graphic design, jenny Conway
Narrator: Ana Alvarez
Keywords: Lesson planning; Teacher effectiveness; Classroom management; Professional development